2012
DOI: 10.1261/rna.030510.111
|View full text |Cite
|
Sign up to set email alerts
|

Meiosis-induced alterations in transcript architecture and noncoding RNA expression in S. cerevisiae

Abstract: Changes in transcript architecture can have powerful effects on protein expression. Regulation of the transcriptome is often dramatically revealed during dynamic conditions such as development. To examine changes in transcript architecture we analyzed the expression and transcript boundaries of protein-coding and noncoding RNAs over the developmental process of meiosis in Saccharomyces cerevisiae. Custom-designed, high-resolution tiling arrays were used to define the time-resolved transcriptome of cells underg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 52 publications
5
29
0
Order By: Relevance
“…They also reported that in the case of uORFs with an AUG start codon, the translational efficiency and ribosome occupancy showed a “strong negative correlation” (Brar et al 2012). A subsequent microarray-based study of meiotic yeast confirmed the presence of abundant transcript architecture changes in meiotic and sporulating yeast (Kim Guisbert et al 2012). …”
Section: Discussionmentioning
confidence: 89%
“…They also reported that in the case of uORFs with an AUG start codon, the translational efficiency and ribosome occupancy showed a “strong negative correlation” (Brar et al 2012). A subsequent microarray-based study of meiotic yeast confirmed the presence of abundant transcript architecture changes in meiotic and sporulating yeast (Kim Guisbert et al 2012). …”
Section: Discussionmentioning
confidence: 89%
“…Given that the budding yeast transcriptome comprises mRNAs, developmental stage-specific mRNA isoforms with extended 5′- and 3′-UTRs and long non-coding RNAs (lncRNAs), it seems reasonable to assume that Ume6 is not only important for the former two transcript categories, but also for RNAs with little or no coding potential (Cho et al 1998; Chu et al 1998; Primig et al 2000; Wyers et al 2005; Nagalakshmi et al 2008; Xu et al 2009; Lardenois et al 2011, 2014; Kim Guisbert et al 2012; Waern and Snyder 2013). Indeed, we have observed by RT-PCR assays that ume6 / ume6 and rpd3 / rpd3 mutant cells cultured in YPD and YPA accumulate a number of lncRNAs, such as meiotic unannotated transcripts (MUTs), cryptic unstable transcripts (CUTs), and stable unannotated transcripts (SUTs) to higher levels than the wild-type control strain (Y. Liu and B. Xie, unpublished).…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Recent studies using tiling arrays and RNA-Sequencing helped explain this puzzling fact: cells induce a long transcript isoform with an extended 5 0 -UTR proposed to inhibit Orc1 translation. 13,29 However, neither microarrays nor RNA-Seq experiments unambiguously show that the 5 0 -extended isoform is synthesized through to the same transcription termination site (TTS) as the short isoform. We propose that data in previously published work and this study are consistent with the notion that both isoforms use a common TTS as the model in Fig.…”
Section: Establishing Developmental Stage-specific Middle Meiotic Isomentioning
confidence: 99%